Riding the alterity. The depiction of pygmy 'warriors' in Roman Nilotic paintings - Voltan, Eleonora (O T I V M, 2023)
In this paper, the focus is on the depiction of pygmies as 'warriors' in Nilotic Roman paintings. After a brief overview regarding the picta nilotica's spread and chronology, a particular attention is turned to the scenes of fighting between pygmies and Nilotic fauna. Furthermore, some aspects that mark this iconographic solution are highlighted: the varied and extravagant 'armour', tools and chargers used by the pygmies to defend themselves against the animal attacks living along the banks of the Nile.